The representation of an instant: Lessing and Ernst Gombrich’s pictographic method - Ignacio Uribe Martínez (Arte, Individuo y Sociedad, 2012)
Although the representation of a single instant as a limitation to figurative arts in Lessing’s Laokoon has been considered by Ernst Gombrich as the origin of a fallacious conception of art, this article shows the affinity between the idea of “pictographic method” displayed by the Austrian historian and the notions of imagination and verisimilitude proposed by Lessing.